Online trigger processing for a small-animal RPC-PET camera - Clemêncio, Filomena M. C. (2011)
A complex task for positron emission tomography (PET) cameras is the design of an appropriate coincidence-detec tion trigger system as it usually encompasses coincidences in a large number of channels and requires tight time specifications. Those requirements are even greater for a resistive plate chamber (RPC)-based detector technology since the time window specifica tion is quite small (in the order of a few hundred picoseconds) and the number of coincidence-channels can be quite large. Previous work showed that the time resolution for gamma photon pairs of a detector based on resistive plate chamber technology is under 300 ps full width at half maximum. This allows for a very tight time window for coincidence detection, with the corresponding benefits in reducing the number of random coincidences observed and, hence, the overall noise on the acquired image. In this paper, we first show experimental results of a coincidence-detection algo rithm implemented inside a Xilinx Virtex-5 field-programmable gate array for a small-animal RPC-PET camera being built.